Temperature and pH driven association in uranyl aqueous solutions - Druchok, M.; Holovk, M. (Condensed Matter Physics, 2012)
An association behavior of uranyl ions in aqueous solutions is explored. For this purpose a set of all-atom molecular dynamics simulations is performed. During the simulation, the fractions of uranyl ions involved in dimer and trimer formations were monitored. To accompany the fraction statistics one also collected distributions characterizing average times of the dimer and trimer associates. Two factors effecting the uranyl association were considered: temperature and pH. As one can expect, an increase of the temperature decreases an uranyl capability of forming the associates, thus lowering bound fractions/times and vice versa. The effect of pH was modeled by adding H⁺ or OH⁻ ions to a "neutral" solution. The addition of hydroxide ions OH⁻ favors the formation of the associates, thus increasing bound times and fractions. The extra H⁺ ions in a solution produce an opposite effect, thus lowering the uranyl association capability. We also made a structural analysis for all the observed associates to reveal the mutual orientation of the uranyl ions. Проведено дослiдження процесiв асоцiативностi у водних розчинах уранiлу. Для цього проведено низку моделювань методом молекулярної динамiки. Пiд час моделювання проведено монiторинг фракцiй iонiв уранiлу, що беруть участь у формуваннi димерiв та тримерiв. Також зiбрано розподiли iмовiрностi за часами життя уранiлових димерiв та тримерiв. Розглянуто вплив двох факторiв – температури та рiвня рН середовища – на здатнiсть iонiв уранiлу до формування асоцiатiв. Виявлено, що збiльшення температури знижує асоцiативнiсть, при цьому також скорочуються часи життя асоцiатiв i зменшуються фракцiї iонiв уранiлу у асоцiатах. Вплив рiвня рН середовища змодельовано додаванням iонiв H⁺ чи OH⁻ до “нейтрального” розчину. Виявлено, що наявнiсть у розчинi iонiв OH⁻ є сприятливим чинником для асоцiативностi, в той час як наявнiсть iонiв H⁺ призводить до протилежного ефекту. Для усiх розчинiв проведено конфiгурацiйний аналiз взаємної орiєнтацiї iонiв уранiлу, що перебувають у асоцiативному станi.